ASSESSING SELF EVALUATION LEVEL OF PRESENTATION SKILLS AMONG EFL MASTER STUDENTS AT SAIDA UNIVERSITY - Abdelkader Makhlouf; Hanane Rabahi; Hamza Maamra (International Journal of Innovative Technologies in Social Science, 2025)
To raise their presentations skills, the students need to be aware about how to prepare and perform an effective presentation. This study aimed at identifying the English language students' self-evaluation level of presentation skills at Saida University, Algeria. Through careful analysis of quantitative data from a 19-item questionnaire administered to 79 first-year master's students in English as a foreign language (EFL) over two separate academic years (2018/2019 & 2019/2020), enlightening conclusions emerged. The results reveal that the students’ self-evaluation level is above average. The study also reveals that there is a significant difference between the male and female students in their awareness level of self- evaluation presentation skills.The results also indicate that there are no differences in the students’ self-evaluation level between the two classes scored in the two different academic years study. This research, anchored in the undergraduate cycle, is committed to ensuring the accuracy of self-assessments, probing gendered disparities and ensuring the consistency of assessments across various academic disciplines. It highlights the urgent need to support students in recognizing and developing their presentation skills.